Kinship in Action: Self and Group - Farid Pazhoohi (Ethnobiology Letters, 2013)
Review of Kinship in Action: Self and Group. Andrew Strathern and Pamela Stewart. 2011. Prentice Hall Publishing, Upper Saddle River, N.J. Pp. 224. US $39.60 (paper). ISBN 100131844849.